Аnаlysis of Potеntiаl, Struсturе, Dynаmiсs of Dеvеlopmеnt of Kаzаkhstаn’s Sсiеnсе - D. M. Mussayeva; G. Zh. Alibekova; Medeni Tunc; M. I. Dabylova (Экономика: стратегия и практика, 2021)
This article analyzes the scientific potential, its structure, and dynamics of development in Kazakhstan to develop strategic recommendations for the further development of science. The main purpose of the scientific work is to obtain accurate data on the state of the dynamics of the development of Kazakh science. The main research methods were generalization, systematization, and the economic and statistical method. The statistical base of the study was the data of the Statistics Committee of the Ministry of National Economy of the Republic of Kazakhstan for the period from 2010 to 2020. According to the analysis, it was revealed that the state budget plays the main role in the financing of R&D in the republic, and the priority direction of R&D is research in the field of engineering developments and technologies. While there are several problems in the field of social sciences and humanities in Kazakhstan: the tendency to reduce the sphere of social sciences, a low proportion of highly qualified personnel in the humanities, a low material and technical base of social and humanitarian research, which is manifested in a high share of labor costs. Positive trends in the growth of costs for R&D, the development of the entrepreneurial sector of science, as well as negative trends in reducing costs for medical sciences were revealed. It is shown that there is a critical situation with the reproduction of scientific personnel, especially highly qualified personnel. The results of the study may be of interest to government authorities in the field of science.